2012
DOI: 10.1002/jcb.24215
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the function of spot in Helicobacter pylori anti‐oxidative stress in vitro and colonization in vivo

Abstract: As a microaerobe, Helicobacter pylori employs the global regulator SpoT for defending against oxidative stress in vitro. However, the mechanisms how SpoT affects bacterial gene expression is still unknown. Moreover, the function of SpoT in H. pylori colonization in the host is remaining undetermined. To explore the functions of the SpoT in H. pylori pathogenesis, we constructed H. pylori 26695 spoT-deficient mutant (ΔspoT). While grown in ambient atmosphere, protein expression profile of the ΔspoT was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In our previous studies, we successfully constructed an spoT mutant strain (the Δ spoT strain) ( 62 ) and an spoT -complemented strain (the spoT* strain) ( 44 ). The plasmids (pILL570 and pUC18K2) used to construct the mutant strain were kindly provided by Agnès Labigne (Unité de Pathogénie Bactérienne des Muqueuses, Institut Pasteur).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we successfully constructed an spoT mutant strain (the Δ spoT strain) ( 62 ) and an spoT -complemented strain (the spoT* strain) ( 44 ). The plasmids (pILL570 and pUC18K2) used to construct the mutant strain were kindly provided by Agnès Labigne (Unité de Pathogénie Bactérienne des Muqueuses, Institut Pasteur).…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids (pILL570 and pUC18K2) used to construct the mutant strain were kindly provided by Agnès Labigne (Unité de Pathogénie Bactérienne des Muqueuses, Institut Pasteur). The construction of the gluP mutant strain was identical to the construction of the Δ spoT strain, as described in a previous study ( 62 ). Briefly, the gluP gene from the genome of H. pylori 26695 was destroyed with the insertion of the nonpolar aphA-3 gene, encoding a kanamycin resistance cassette.…”
Section: Methodsmentioning
confidence: 99%
“…Co-culture of a gastric non-cancer epithelial cell line with coccoid or helical forms of Hp revealed that helical Hp led to more severe inflammatory and apoptotic responses, while coccoid Hp maintained host cell in a high proliferation rate (Liu et al, 2006). Interestingly, in animal models, colonization efficiency of Hp mutants in coccoid associated genes, aimA and spoT , was markedly reduced (Sun et al, 2012; Chaput et al, 2016). Despite substantial contrasting findings in the observations, overall, accumulated data suggest that coccoid Hp retains virulence, can survive better in vivo and may contribute to carcinogenesis, while helical Hp can be more easily eliminated by acute host immunoinflammatory responses.…”
Section: Functional and Morphological Changes Associated With Biofilmmentioning
confidence: 99%
“…pylori strains used in this study were reference strain 26695, which was kindly provided by Zhang Jianzhong (Chinese Disease Control and Prevention Center), and its isogenic spoT mutant, which was used in our previous report and comes from the collection of our laboratory (52). All E.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of hp0939 , hp1017 , hp0497 , and hp0471 mutant strains was identical to the construction of the Δ spoT strain, as described in the literature (52). Briefly, these four genes from the genome of H.…”
Section: Methodsmentioning
confidence: 99%